Ethnomathematics: Exploration of Traditional Balinese Flute as Mathematics Learning Resources - I Wayan Puja Astawa; I Made Adi Wira Nata Putra; I Gusti Putu Suharta (Universitas Pendidikan Ganesha, 2022)
The local culture of the community is a very rich source of learning. The use of Balinese culture in learning mathematics is still limited and needs to be studied more broadly and in depth. This research aims to analyse the ethnomathematical elements contained in the Balinese flute, to point out the potential application of the Balinese flute in mathematics learning, and to analyse how Balinese flute artists acquire knowledge. This research is qualitative research with an etnographic approach using three subjects of Balinese flute craftsmen and one Balinese flute artist. The research subjects were three Balinese flute craftsmen and a Balinese flute artist. Data were collected by using three methods such as literature study, observation, and interviews. The collected data were then analysed descriptively using domain analysis, taxonomy analysis, componential analysis, and analysis of cultural themes. This research found that the ethnomathematical elements contained in the Balinese flute are local terms related to measurement and measuring techniques, mathematical sequences, and concepts of geometry. This flute has potentials utilization as a source of contextual mathematics learning for student at junior and senior high schools. In addition, it is found that knowledge of Balinese flute possessed by craftsmen was obtained from self-learning and from their ancestors’ legacy.